PROGRAM LITERASI MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS III B SDN 20 KAMPUNG LORONG - Fauzan Al Fiqri (Lunggi Journal, 2025)
ABSTRACK The objectives of this study are: (1) To describe the implementation of the literacy program in improving the speaking skills of third-grade B students at SDN 20 Kampung Lorong. (2) To describe the impact of the literacy program on third-grade B students at SDN 20 Kampung Lorong. (3) To describe the obstacles experienced by third-grade B students at SDN 20 Kampung Lorong regarding the literacy program in improving speaking skills. This research employs a qualitative approach with a field research design. Data collection techniques used in this study include interviews, observation, and documentation. The data analysis techniques applied are data condensation, data display, and conclusion drawing/verification. To ensure the validity of the data, source triangulation and member checks were used. The results of this study indicate that: (1) The implementation of the literacy program for third-grade students involves three stages: the habituation stage, the development stage, and the learning stage. In the habituation stage, students engage in read-aloud and silent reading activities. In the development stage, students are trained to recognize punctuation, pronunciation, and intonation. However, the learning stage has not yet been implemented in class III B. (2) There are five impacts of the literacy program: it improves language skills, increases reading interest, enhances learning motivation, develops communication skills, and improves writing ability. (3) There are two types of obstacles students face in improving their speaking skills: internal and external factors. Internal factors include imperfections in speech organs, language components, content components, as well as fatigue and health. External factors include noise, room conditions, and the listener's knowledge. Keywords: Literacy Program, Speaking Skills. ABSTRAK Tujuan penelitian ini adalah (1). Mendeskripsikan penerapan program literasi dalam meningkatkan keterampilan berbicara siswa kelas III B di SDN 20 Kampung Lorong. (2). Mendeskripsikan dampak dari program literasi terhadap siswa kelas III B di SDN 20 Kampung Lorong. (3) Mendeskripsikan hambatan yang dialami siswa kelas III B di SDN 20 Kampung Lorong terhadap program literasi dalam meningkatkan keterampilan berbicara. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan field research. Teknik pengumpulan data pada penelitian ini menggunakan teknik wawancara, observasi, dan dokumentasi. Teknik analisis data yang digunakan yaitu kondensasi data, penyajian data, dan penarikan kesimpulan/verivikasi. Teknik pemeriksaan keabsahan data menggunakan triangulasi sumber dan member check. Hasil dari penelitian ini menunjukkan bahwa (1). Peserta didik kelas III pada penerapan program literasi menggunakan 3 tahapan yaitu, tahap, pembiasaan, tahap pengembangan, dan tahap pembelajaran. Pada tahap pembiasaan siswa menggunakan model membaca nyaring dan membaca dalam hati, sedangkan pada tahap pengembangan siswa dilatih untuk mengenal tanda baca, pelafalan, serta intonasi, dan pada tahap pembelajaran siswa kelas III B belum melaksanakannya. (2). Terdapat 5 dampak yang dihasilkan dari program literasi, meningkatkan keterampilan berbahasa, meningkatkan minat membaca, meningkatkan motivasi belajar, mengembangkan kemampuan berkomunikasi dan meningkatkan kemampuan penulisan. (3) Terdapat 2 penghambat siswa dalam meningkatkan ketrampilan berbicara yaitu dari faktor internal dan eksternal. Faktor Internal meliputi ketidaksempurnaan alat ucap, komponen kebahasaan, komponen isi serta kelelahan dan kesehatan. Adapun faktor eksternalnya yaitu suara atau bunyi, kondisi ruangan dan pengetahuan pendengar. Kata Kunci: Program Literasi, Keterampilan Berbicara